Rola instytucji gospodarki społecznej w rozwiązywaniu problemów społecznych - Kietlińska, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Negative social phenomena like poverty, unemployment and disability escalate in many countries, including Poland. Governments activities that were to decrease size of those situations caused not only awakening of nonprofit sector but also awakening of private sector interested in employing marginalized people. It opened doors for social sector with its new functional forms like social companies of co-operative societies. It can work thanks to state and local authorities as well as nonprofit organizations systematic help. The main purpose of this article is to show new organizational forms as well as to grade them. The analysis will focus on institutions that were introduced in Poland under legislative acts. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 26-39